2014
DOI: 10.1371/journal.pone.0115212
|View full text |Cite
|
Sign up to set email alerts
|

Reading the Mind in the Eyes or Reading between the Lines? Theory of Mind Predicts Collective Intelligence Equally Well Online and Face-To-Face

Abstract: Recent research with face-to-face groups found that a measure of general group effectiveness (called “collective intelligence”) predicted a group’s performance on a wide range of different tasks. The same research also found that collective intelligence was correlated with the individual group members’ ability to reason about the mental states of others (an ability called “Theory of Mind” or “ToM”). Since ToM was measured in this work by a test that requires participants to “read” the mental states of others f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
203
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(229 citation statements)
references
References 55 publications
10
203
2
Order By: Relevance
“…The average social perceptiveness of the team members is predictive of collective intelligence [11]. Second, in both laboratory and field studies, researchers have found that greater amounts of participation and more equal participation are associated with higher collective intelligence [8,11].…”
Section: Collective Intelligencementioning
confidence: 99%
“…The average social perceptiveness of the team members is predictive of collective intelligence [11]. Second, in both laboratory and field studies, researchers have found that greater amounts of participation and more equal participation are associated with higher collective intelligence [8,11].…”
Section: Collective Intelligencementioning
confidence: 99%
“…They found, "surprisingly, the most important ingredients for a smart team remained constant regardless of its mode of interaction: members who communicated a lot, participated equally and possessed good emotion-reading skills." 15,16 Consistent with this study,…”
Section: Meetsupporting
confidence: 87%
“…This test has been applied in several experience related with collective intelligence measure applied for getting the level of social sensitivity [6][16] [4][16]. In this test, a participant is presented with a series of 35 photographs of the eye-region of the face of different actors and actresses, and is asked to choose which of four words best describes what the person in the photograph is thinking or feeling.…”
Section: Reading the Mind In The Eyes Testmentioning
confidence: 99%